Hubungan Karakteristik Individu, Kepatuhan Minum Obat dan Kondisi Fisik Rumah dengan Kejadian Tidak Konversi Pasien Tuberkulosis di Kabupaten Klaten - Saras Kuntari; Achmad Husein; Sigid Sudaryanto (Poltekkes Kemenkes Yogyakarta, 2012)
The finding of new BTA positive of TB cases in Klaten Regency showing an increase from year to year, yet this condition were accompanied by the increaseof the incidence of inconvertion. The failure of convertion of a TB case will make someone still become a source of TB bacteria transmission. The objective of this re-search was to determine the risk factors of the inconvertion. The explored variables were age, educational level, nutrional status, medicinal obedience, house humidity, house illumination and house density. The researchwas conducted between May – July 2011 and employed case-control design. In case group there were 35 TB patients with new BTA positive who did not convert, and by following 1 : 1 ratio, 35 control were included in the control group. Those study subjects were registered in Klaten’s Health Agency between January – September 2010 and came from community health centers and hospitals which have followed the DOTS program. Data were obtainedthrough questionnaires and direct interviews as well as observation and direct measurement. Apart from univariate analysis, the data were also analysedbivariately by using chi square test, and followed by multivariate analysis using logistic regression test. The results shows that medicinal obedience was theprimary risk factor of con-version failure with OR = 5,542; 95% CI = 1,760 to 17,449 and p value = 0,003. It is advised for TB patients that together with theimportance of proper and on-scheduled medication, good nutrion intake for supporting the recovery and healthy home enviroment should be included fortheir concern.